How to save it and how it saves us : built heritage and disaster / Erna Meutia ... [et al.] - Meutia, Erna; Dewi, Cut; Izziah, Izziah; Saleh, Muhammad (2018)
Banda Aceh is the capital of Aceh province that is located on the north end of Sumatra, Indonesia. As one of the cities lies above the Indo-Australia tectonic plate, on December 26, 2004, a tectonic earthquake with magnitude of 9.2 scales Richter caused tsunami waves, which caused destruction of the whole town. The connection between cultural heritage and disaster has always being linked with cultural heritage, which is seen as a burden and something that has to be protected. Protecting the cultural heritage from destruction such as from disaster has always been associated with the continuity of the society’s identity. However, the cultural heritage is not always a passive victim in a disaster, cultural heritage can also play an active role in giving power and helping people to rise from difficult times after a disaster.This study is part of the whole project of mapping and zoning built-heritage in Banda Aceh by using a digital humanities approach combining several methods such as mapping, GIS, interview, and participant observation. In this paper we present a partial finding of interview with 252 repondents in Banda Aceh about their perception of heritage and their stories of heirtage and disaster. The goal of this study isto understand how cultural and disaster protection are linkedin the perspective of cultural heritage as active agents